Assessment of Natural Variation in OsHKT1;2 Gene in Rice (Oryza sativa) - Phuc, Do Thi; Minh, Nguyen Van; Yen, Hoang Hai (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: HKT gene family encodes Na + and/or K + transporter located on cellular membrane in plants. HKT transporter family has been proven to play a crucial role in maintaining low Na + /K + ratio to help plant survive during saline condition. OsHKT1;2 gene is a member of rice HKT gene family. However, the functional roles of the OsHKT1;2  is reminded unknown. In this study, we investigated the natural variations in coding sequence of OsHK1;2 . Firstly, the coding sequence of OsHKT1;2 was amplified by PCR using specific primers in 13 different rice cultivars, then the PCR products were directly sequenced. The results revealed two nucleotide variations at position 343 and 1413 in eight rice cultivars. However, the predicted amino acid sequence showed three early stop codons presenting within the exon 1 in all 13 investigated rice cultivars, suggesting that OsHKT1;2 might be a pseudogene that might not produce full-length protein.  Keywords: OsHKT1;2 rice, salt stress, natural variation.